Cost-effectiveness of percutaneous patent foramen ovale closure versus medical therapy for cryptogenic stroke prevention: A Chinese healthcare perspective - Chen Chen; Ting Xu; Zhujun Zeng; Jing Miao; Rong Hu; Yiming Gao; Chunlin Li; Meng Li; Xiaoli Yang (PLoS ONE, 2026)
Background Patent foramen ovale occurs in approximately 25% of cryptogenic stroke patients, with paradoxical embolization representing a key pathophysiological mechanism. While recent trials have established the clinical efficacy of percutaneous PFO closure in reducing recurrent stroke risk, comprehensive economic evaluation within the Chinese healthcare framework remains limited. This study assessed the cost-effectiveness of PFO closure compared with medical therapy alone in Chinese patients with cryptogenic stroke. Methods A Markov cohort model was constructed with four health states (stable, post-minor recurrent stroke, post-moderate-to-severe recurrent stroke, death) using 3-month cycles over a 30-year horizon. The analysis adopted a Chinese healthcare payer perspective, incorporating transition probabilities derived primarily from the RESPECT trial extended follow-up data and Chinese-specific cost data from multi-center hospital surveys. Primary outcome was the incremental cost-effectiveness ratio (ICER) evaluated against China’s willingness-to-pay threshold of $37,654 per quality-adjusted life year (QALY). Extensive sensitivity analyses examined parameter uncertainty and model robustness. Results PFO closure demonstrated economic dominance over medical therapy, yielding 1.41 additional QALYs (13.42 vs 12.01) while reducing lifetime costs by $4,045 per patient ($8,847 vs $12,892). The resulting negative ICER of -$2,868 per QALY indicated superior outcomes at lower cost. Probabilistic sensitivity analysis revealed 94.2% probability of cost-effectiveness at the Chinese threshold. One-way sensitivity analyses consistently showed negative ICERs across all parameter ranges, with time horizon and psychological comorbidity costs exerting the greatest influence on results. Conclusions In the Chinese healthcare context, PFO closure represents a dominant economic strategy for cryptogenic stroke patients, providing both clinical benefits and cost savings. These findings support broader implementation of PFO closure programs and inform evidence-based resource allocation decisions for stroke prevention services.